Phenomenological Approaches In Religious Studies (International Journal of Scientific Research and Management (IJSRM), 2023)
Phenomenology of religion is a development movement in thought and research where researchers try to understand humans and classify phenomena specifically including religious phenomena. The purpose of this study is to study and analyze in depth related to phenomenological approaches in religious studies.this research is a review literature research using descriptive methods. Data collection is carried out by means of record, listen and record techniques. The research steps carried out include collecting data, reducing data, and analyzing data to describe phenomenological approaches in religious studies. The results of this study show that Phenomenology and then Religious Phenomenology is a new approach in conducting studies of religion, although theologically and methodologically religious phenomenology is still a debate among religious scientists, this approach is able to explore the deeper meaning of a religious phenomenology, in addition to being able to be a middle ground for philosophical and theological approaches in revealing religious phenomena. Approaches in religious studies that separate religion from the sacred, transcendent, hefty forces liberate religion from theology, and religious phenomenology has its context in this regard.